ADSORPTION OF PHENOL POLLUTANTS FROM AQUEOUS SOLUTION USING Ca-BENTONITE/CHITOSAN COMPOSITE (Adsorpsi Polutan Fenol dari Larutan Berair Menggunakan Komposit Ca-Bentonit/Kitosan) - Poedji Loekitowati Hariani; Fatma Fatma; Fahma Riyanti; Hesti Ratnasari (Jurnal Manusia dan Lingkungan, 2015)
Phenolic compounds areorganic pollutants that are toxic and carcinogenic.The presence of phenol in the environmentcan be adverse to humanand the environmentalsystem. One methodthat iseffective toreduce thephenolisadsorption. In this study, the adsorption of phenol in aqueous solution using Ca-bentonite/chitosan composite was investigated. Chitosan is the deacetylation product of chitin from shrimp waste. Characterization of Ca-bentonite/chitosan composite was done by using Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy-Energy Dispersive X Ray Spectroscopy (SEM-EDX). Batch adsorption studies were performed to evaluate the effects of some parameters such as initial concentration of phenol, composite weight, pH and contact time. The results showed that FTIR spectra of Ca-bentonite/chitosan composite presented the characteristic of peak of Ca-bentonite and chitosan that confirmed the successful synthesis of composite. The SEM-EDX characterizationresultsshowedCa-bentonite surfacecoverage by chitosanand the presence ofcarbonandnitrogenelementsinCa-bentonite/chitosancompositeindicated that chitosan had bonded with bentonite. The optimum condition of adsorption of Ca-bentonite/chitosan to phenol was obtained at 125 mg.L-1 of concentration in which the weight of composite was 1.0 g, the pH of solution was 7, the contact time was 30 minutes, and the capacity of adsorption was 12.496 mg.g-1.